miRNA Expression Response of Aedes aegypti (Linnaeus 1762) (Diptera: Culicidae) to Imidacloprid Exposure - Gerardo Trujillo-Rodríguez; Mariana Lizbeth Jiménez-Martínez; Elda Flores-Contreras; Everardo González Gonzalez; María de Lourdes Ramírez Ahuja; Idalia Garza Veloz; Adriana E. Flores Suarez; Fabian Correa Morales; Felipe Dzul Manzanilla; Iram P. Rodriguez Sanchez; Margarita L. Martínez Fierro (Insects)
Aedes aegypti is a major vector of arboviruses, including dengue, Zika, chikungunya, yellow fever, and Mayaro. The extensive use of insecticides has led to resistance, complicating vector control efforts. MicroRNAs (miRNAs) are post-transcriptional regulators involved in detoxification and stress adaptation; however, their role in the insecticide response of Ae. aegypti remains unclear. This study analyzed miRNA expression in Ae. aegypti following imidacloprid exposure, comparing a field strain, Martinez de la Torre from Mexico (MT), and a susceptible reference strain, New Orleans (NO). Small RNA sequencing identified 96 miRNAs, with miR-1, miR-281-5p, miR-100, and miR-184 being consistently expressed across all conditions. In contrast, let-7, miR-124, and miR-13-3p were exclusively detected in wild mosquitoes exposed to imidacloprid, while miR-14 and miR-275-3p showed condition-specific expression. Distinct miRNA expression patterns were observed between the field and susceptible strains, with specific miRNAs showing condition-dependent expression. These findings suggest that certain miRNAs may serve as potential biomarkers for resistance monitoring, contributing to a better understanding of insecticide response mechanisms and informing novel vector control strategies.